Clinicopathology of induced molybdenum toxicity in young goats - SHARMA, A K; PARIHAR, N S (The Indian Journal of Animal Sciences, 2013)
Young nondescript goats (20) and of either sex were allocated to 3 groups of 8,8 and 4 goats. These goats received additional molybdenum @ 50, 100 and 0 ppm (groups 1,2, 3) of feed (DM) in the form of drench of ammonium molybdate solution daily for 235 days. Clinical signs developed earlier in goats of group 2, Diarrhoea, anaemia, reduced body weights, weakness, unthriftiness, depigmentation of the hair and altered reproductive performance were the important clinical manifestations. Anaemia, leucopaenia, hypoproteinaemia, transient hyperglycaemia, reduced levels of serum copper and ceruloplasmim were the important clinicopathological observations. It was concluded that the excess of molybdenum feeding in goats not only produced hypocuprosis but also certain alterations which could be specifically attributed to toxic effects of molybdenum.